Design and Build System Applications Design and Build Information System Applications IT Infrastructure Training and Training - Fahmi Iskandar; Zulham Sitorus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
To speed up IT infrastructure training for employees in the information technology department, PT. Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch needs to change its current conventional training management to information technology based. This is needed because the large number of employees and large areas require efficiency in organizing training. The proposed solution is the development of a web-based information system using PHP and MySQL to make it easier to manage training and access information for organizing staff wherever they are. Web-based IT Infrastructure Training uses a PHP program with a MySQL Database so it is hoped that this information system can help the Administration Section staff to easily access information about training from anywhere and at any time using internet facilities